Yield performance of several peanut cultivars grown in dryland with semi-arid climate in Sumba Timur, Indonesia - Agustina Asri Rahmianna; Andy Wijanarko; Joko Purnomo; Yuliantoro Baliadi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Rahmianna A, Wijanarko A, Purnomo J, Baliadi Y. 2020. Yield performance of several peanut cultivars grown in dryland with semi-arid climate in Sumba Timur, Indonesia. Biodiversitas 21: 5747-5757.  Peanut (Arachis hypogaea L.) is the fourth major food crops in Indonesia after rice, maize, and soybean. The seeds contain oil, protein, and carbohydrate which are beneficial to human health. Despite its health benefit, farmers sell all pods for cash. The dryland areas with semi-arid climates, where there is only one growing season, are the potential areas for peanut cultivation. The experiment was conducted to assess the performance of improved cultivars grown in dryland with low rainfall at Sumba Timur District of East Nusa Tenggara Province, Indonesia during February-May 2017. Ten improved peanut cultivars and one local cultivar were grown in two sites: Laipori and Palakahembi Villages. A randomized block design with three replicates was applied in each site. The treatment was peanut cultivar, i.e., Local Sandel, Bison, Gajah, Hypoma 1, Hypoma 2, Kancil, Kelinci, Takar 1, Talam 1, Talam 2, and Tuban that belonged to Spanish type except Kelinci that was a Valencia type. A 100 kg ha-1 of composite NPK fertilizer was applied at sowing time, and the water source was merely from rainfall. Captan fungicide was applied as seed treatment, and Deltamethrin insecticide were applied two times during the growing period. The results indicated that the improved cultivars performed better than the local cultivar, i.e., their pod yields were 1.75-2.57 times higher than that of Local Sandel. Hypoma 1 cultivar gave the highest yield with 2.313 t ha-1 of dry pod yields or 257% higher than that of Local Sandel. In addition to high pod yield production, Hypoma 1 also produced 6.1 t ha-1 fresh haulms, and those of improved cultivars were 5.3-7.2 t ha-1. In summary, the improved cultivars, especially Hypoma 1 is highly recommended for cultivation by the farmers in Sumba Timur because of their high pod yields and organic matter content in soils after the plants harvested.